The European Central Bank and the European macroeconomic constitution : from ensuring stability to fighting crises - Tuori, Klaus (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
The book is about money, central banking and constitutions. It explains how the European Central Bank was established to ensure stability and prosperity for the euro area. The ECB was guided and controlled by a coherent European Macroeconomic Constitution. However, this model has failed during recurring crises, and the ECB has started to act as the euro area fire brigade. Consequently, it is pushing the boundaries of monetary policy, and with that challenging the accountability mechanisms and fundamentally also the democratic legitimacy of the EMU. The book sheds light on this complex economic-constitutional setting with a view on the future. The imbalance between various new operations and a single price stability objective is difficult to remedy. New objectives of financial stability, economic adjustment and environmental sustainability can cause fundamental ruptures between the ECB's formal role and its actions, and they also dangerously overburden monetary policy moving forward with substantial risks.
Introduction - a supranational central bank as a subject -- The three foundations of the EMU -- The principles of the European macroeconomic constitution -- ECB organisation, monetary policy strategy and operational framework -- ECB monetary policy during the financial crisis -- The prelude to the sovereign debt crisis : events, ECB verbal interventions and EU rescue programmes -- Selective government bond purchases -- The ECB's Quantitative Easing -- The banking union - the ECB takes over banking supervision -- ECB measures during the covid-19 pandemic -- The fate of the European macroeconomic Constitution -- The objectives for the ECB and the Macroeconomic Constitution going forward -- Epilogue : where do we go from here?
Title from publisher's bibliographic system (viewed on 20 Sep 2022).
Keywords: European Central Bank; Banks and banking, Central -- Law and legislation -- Economic aspects -- European Union countries; European Union countries -- Economic policy